A comparative applied study of the Springett-Jordan, Kidda and Zmejewski models for predicting financial failure (Journal of Hama University, 2025)
The research aimed to measure and predict the financial failure of the American retail company Wal-Mart. It also aimed to clarify the most important theoretical foundations of financial failure, and to introduce the Springett-Jordan, Zmejewski, and Kidda models of financial failure, and to determine their reality and the extent to which they predict the risks of financial failure, and whether these models are applied in the research. It indicates the risks of expected financial failure to the same degree, as well as providing information about these models to financial managers, and how to apply them and develop their risk management skills. Among the most important conclusions that were reached: there was consistency in the results of all models, as they indicated the strong financial position of Wal-Mart and the absence of risks of financial failure.